Bimekizumab Efficacy in High-Impact Areas: Pooled 2-Year Analysis in Scalp, Nail, and Palmoplantar Psoriasis from Phase 3/3b Randomized Controlled Trials - Joseph F. Merola; Alice B. Gottlieb; Andreas Pinter; Boni Elewski; Melinda Gooderham; Richard B. Warren; Stefano Piaserico; Krista Wixted; Nancy Cross; Nicola Tilt; Susanne Wiegratz; Ulrich Mrowietz (Adis, Springer Healthcare, 2024)
Abstract Introduction Psoriasis in high-impact areas, including the scalp, nails, palms, and soles, can disproportionately impair patient quality of life. Here, we evaluate the 2-year efficacy of bimekizumab treatment in patients with moderate to severe plaque psoriasis in post hoc analyses of five phase 3/3b trials. Methods High-impact area efficacy data were pooled through 2 years across five phase 3/3b trials: BE VIVID, BE READY, BE SURE, their ongoing open-label extension (OLE) BE BRIGHT, and BE RADIANT (including its double-blinded treatment period and the first year of its OLE). Complete clearance of psoriasis in high-impact areas is reported over 2 years using the scalp Investigator's Global Assessment (IGA), palmoplantar IGA, and modified Nail Psoriasis Severity Index (mNAPSI). Patients included in these analyses had baseline moderate to severe scalp or palmoplantar involvement (scalp or palmoplantar IGA score ≥ 3) or mNAPSI score > 10. Results A total of 1107 patients were randomized to bimekizumab and entered the OLEs. Subsets of 821 patients had scalp IGA ≥ 3 at baseline, 377 had mNAPSI > 10, and 193 had palmoplantar IGA ≥ 3. Complete scalp clearance in patients with baseline scalp IGA ≥ 3 randomized to bimekizumab was achieved rapidly, with high responses sustained from first (86.4%) to second year (85.9%). Nail clearance responses in patients with baseline mNAPSI > 10 increased from 63.4% to 68.5% from first to second year. Palmoplantar clearance in patients with baseline palmoplantar IGA ≥ 3 was sustained from first (88.3%) to second year (89.8%). Similar trends were seen in the 374 patients who received bimekizumab 320 mg every 4 weeks (Q4W)/every 8 weeks (Q8W) initial/maintenance dosing. Conclusion In these analyses pooled across 2 years, bimekizumab showed sustained efficacy in psoriasis in high-impact areas. Clinicaltrials.gov Trial Registration Numbers NCT03370133, NCT03410992, NCT03412747, NCT03598790, NCT03536884.